PENGARUH KEMAMPUAN MANAJEMEN DIRI MELALUI PENERAPAN MODEL PjBL TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMPN 1 PANGKATAN - Winata Winata; Sakinah Ubudiyah Siregar; Nurlina Ariani Harahap (Universitas Bhinneka PGRI, 2025)
The objective of this study is to examine how students' self-management affects their learning outcomes in mathematics. Time management, self-control, self-motivation, prioritization, and self-reflection are all components of self-management. This research methodology combines a quantitative approach and descriptive analysis. Thirty-four pupils from class VIII3 SMPN 1 Pangkatan made up the research sample. Students used the Cluster Random Sampling technique to determine this. A questionnaire with 30 items to gauge students' self-management and test scores to determine their learning. The outcomes were used to collect data for this study. The data for this study was processed using the SPSS 22.0 program, with paired sample t-tests. The test results show a significant difference between the two variables (t-value = -16.33, significance level = 0.000). With a significance level of 0.000 (less than 0.05). The null hypothesis (H₀) that there is no difference between the two variables is rejected as the significance value is less than 0.05. This implies that there is an impact or relationship between self-management skills and student learning outcomes.